Oral Presentations Abstracts: THE CONCEPT OF VULNERABILITY IN AGED CARE: A SYSTEMATIC REVIEW OF ARGUMENT-BASED ETHICS LITERATURE - SANCHINI, Virginia; SALA, Roberta; GASTMANS, Chris (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Background. Vulnerability is a key concept in traditional – as well as contemporary – bioethics and medical ethics (Ten Have 2015, 2016). Within this literature, the concept of vulnerability is mostly defined in relation to autonomy: vulnerability refers to conditions of impaired and/or diminished autonomy (Belmont Report 1979; CIOMS 1991, 1993, 2002; WMA 2000, 2008; Bracken-Roche et al. 2017). Historically, vulnerability has been associated with several categories of agents, amongst which the elderly are paramount. However, no clear and unique conceptualization of vulnerability, when referred to the ageing population, is currently present – especially in domains other than research ethics: some refer to physiological degradation as a defining tenet, some others appeal to autonomy impairment, some others point to loneliness and isolation (Kahana et al. 1995; Slaets 2006; Dodds 2007; Andrew et al. 2008: Sternberg et al. 2011; Clegg et al. 2013). To fill this gap, we examined the meaning, foundations, and uses of vulnerability as ethical concept in the literature of aged care. Method. Using PRISMA procedure, we conducted a systematic review of argument-based ethics publications in 4 major databases (Pubmed, Embase, Web of Science, and Philosopher’s Index) of biomedical, philosophy, bioethical, and anthropological literature that focused on vulnerability in aged care. 5,735 results were obtained. Titles and abstracts were all screened. We are now in the process of full articles screening. All includes articles will then be critically analyzed. The results of this analysis process as well as a critical reflection on the results will be presented at the EACME conference.